2000
DOI: 10.1149/1.1393312
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Aluminosilicates from Mixtures of SiCl[sub 4], AlCl[sub 3], CO[sub 2], and H[sub 2]

Abstract: A comprehensive study of the chemical vapor codeposition of silica, alumina, and aluminosilicates from SiCl 4 -AlCl 3 -H 2 -CO 2 mixtures is presented. A hot-wall reactor, coupled to an electronic microbalance, is used to investigate the dependence of the deposition rate on temperature, pressure, composition, and total flow rate over a broad range of operating conditions. The experimental observations are discussed in the context of the results obtained in independent deposition experiments of silica and alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…A region of rather weak variation of the deposition rate precedes the maximum in the case of MTS, and therefore, it may be possible to have a situation where the deposition rate does not change significantly over the length of the reactor. As we will see in the following section, the differences in the rates of silica deposition from MTS and SiCl 4 are in agreement with the experimental results [1,66].…”
Section: Overall Modelsupporting
confidence: 87%
See 2 more Smart Citations
“…A region of rather weak variation of the deposition rate precedes the maximum in the case of MTS, and therefore, it may be possible to have a situation where the deposition rate does not change significantly over the length of the reactor. As we will see in the following section, the differences in the rates of silica deposition from MTS and SiCl 4 are in agreement with the experimental results [1,66].…”
Section: Overall Modelsupporting
confidence: 87%
“…A hot wall, tubular chemical vapor deposition reactor has been used in our laboratory to obtain the experimental data [1,58] that we will use to validate the predictions of the kinetic model that we formulated in the preceding sections. The diameter of this reactor is much smaller than its length, and thus, a plug-flow reactor [59] will be used to model it.…”
Section: Transport and Reaction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Further studies revealed that manipulation of the temperature and pressure, and of the residence time of the mixture in the reactor, offered a way of controlling the composition of Al 2 O 3 and SiO 2 in the codeposited films, and shifting the composition towards alumina. [19] The content of the Al 2 O 3 in the deposit was found to increase with decreasing system pressure, increasing temperature, and operation at locations close to the entrance of the reactor.…”
Section: Proposed Scheme For the Preparation Of A Graded Mullite/alummentioning
confidence: 99%
“…A hot-wall CVD reactor of tubular configuration was used for the preparation of the coatings. The results of previous experimental studies on the preparation of aluminosilicate and mullite coatings [18,19] were employed to identify operating conditions under which the deposition of coatings with an Al 2 O 3 content equal to or greater than that corresponding to stoichiometric mullite had proved to be feasible. The development of the graded coatings exploits a key finding of our previous study, [19] viz., a decrease in residence time of the reactive mixture in the reactor has a positive effect on the incorporation of Al 2 O 3 in the deposit.…”
Section: Introductionmentioning
confidence: 99%